" . but imagine the hype for next year's Grey Cup between the Sacramento Argonauts and the San Antonio Eskimos" - Krieger, Bob (The Province, 1992)
" . but imagine the hype for next year's Grey Cup between the Sacramento Argonauts and the San Antonio Eskimos"